Internet addiction among dental students in Malaysia - Radeef Al-Ani, Ali Sabri; Faisal, Ghasak Ghazi (University of Dicle, 2019)
Background: Excessive use of internet by undergraduate students can be pathological which may result in internet addiction (IA) that has negative consequences such as decline in academic performance, social isolation and emotional disturbances. This study aims to assess pathological internet use and its association with psychological distress among dental students. Methods: A sample of 257 dental students from International Islamic University Malaysia participated in this study. Internet addiction was assessed using Chen Internet addiction Scale while the psychological distress was assessed using the 12-item General Health Questionnaire (GHQ-12). Results: The prevalence of IA among dental students was found to be 29.2% while 12.5% were at higher risk for addiction. No significant differences in terms of gender and other socio-demographic factors were found. IA is significantly higher among students with poor social interaction and in those who are using internet for more than 40 hours per week. IA was significantly associated and positively correlated with psychological distress. Conclusions: IA is considerably high among dental students. Male and female students are equally affected. IA has a positive correlation with psychological distress symptoms.